Depressive and Anxiety Symptoms Among People Under Quarantine During the COVID-19 Epidemic in China: A Cross-Sectional Study - Yan, Tong; Zhizhong, Wang; Jianzhong, Zheng; Yubo, Ying; Jie, Liu; Junjun, Zhang; Guangtian, Liu (Frontiers in Psychiatry, 2021)
Background Under the coronavirus disease 2019 (COVID-19) pandemic, quarantine as an effective public health measure has been widely used in China and other countries to slow down the spreading while the psychological response of those high-risk exposed population remains under-reported. Objective To investigate the prevalence of and correlators of psychological distress in the individuals quarantined during the COVID-19 pandemic in China. Methods A online survey was conducted from February 29th to April 10th, 2020, among individuals quarantined at least two weeks due to the high-risk exposure. Chinese versions of the 9-item Patient Health Questionnaire (PHQ-9) with 7-item Generalized Anxiety Disorder (GAD-7) were applied to assess psychological distress. Comply with quarantine and knowledge to the COVID-19 questionnaire was also completed by participants. Unconditional logistic regression model performed to identify the correlators of psychological distress. Results A total of 1,260 participants finished the full survey and included in the data analysis. The prevalence of depression, anxiety, and combination of depression and anxiety (CDA) were 14.0% (95% CI:12.2%-16.1%), 14.8% (95%CI: 13.0%-16.9%), and 6.3% (95%CI: 5.1%-7.8%), respectively. Multivariate analysis showed that people with an undergraduate or above degree more likely to report depression symptoms (OR=2.98, 95%CI:1.56-5.72 ) and anxiety symptoms (OR=2.95, 95%CI:1.14-7.63). Those who were unemployed (OR=0.37, 95%CI:0.21-0.65 for depression; OR=0.31, 95%CI:0.14-0.73 for anxiety ), students (OR=0.14, 95%CI:0.04-0.48 for depression; OR=0.11, 95%CI:0.01-0.85 for anxiety), more knowledgable of COVID-19 (OR=0.84, 95%CI:0.73-0.96 for depression; OR=0.82, 95%CI:0.68-0.98 for anxiety) were less likely to report psychological distress. Higher behavioral compliance scores toward quarantine measures correlated with a lower risk of depression symptoms (OR=0.94, 95%CI:0.91-0.96) and anxiety symptoms (OR=0.95, 95%CI:0.91-0.98). Conclusion The quarantine experiencing during the COVID-19 pandemic may lead to remarkable psychological distress. Consequently, interventional programs target knowledge of COVID-19 should be taken to reduce psychological distress, and comfort the quarantined individuals.